Physiological Responses, Fear-Related Behaviour And Meat Quality Of Broiler Chickens Subjected To Transportation And Other Stressors - Ahmed Al-Aqil, Abdulaziz (2009)
Five experiments were conducted to investigate the effects of pre-slaughter process and other stressors on adrenocortical (CORT) reaction, heterophil and lymphocyte ratios (HLR), fear-related behaviour (TI), meat quality, heat shock protein (hsp) 70 expression, performance, mortality and some blood parameters in broiler chickens. In Experiment I, 200 day-old broiler chickens (Cobb x Cobb) showing short or long tonic immobility responses were classified as low-fear (STI) or high-fear (LTI) responders, respectively. On day 41, they were subjected to either crating or heat challenge (34+1oC) for 3 h and its effect on plasma corticosterone concentration, heterophil/lymphocyte ratios and heat shock protein 70 expression in brain tissue were determined. Crating and heat exposure elevated heterophil/lymphocyte ratios in both STI and LTI birds. Circulating corticosterone, however, was higher in LTI than STI birds following crating and heat challenge. Although differences between fear responder groups for hsp 70 were negligible prior to heat challenge, following 3 h of heat exposure, the response was greater for the LTI than the STI group. Both STI and LTI showed similar increases in hsp 70 following crating. In Experiment II, 432 day-old broiler chicks (Cobb x Cobb) were housed either in an (i) environmentally controlled house (CH) which was maintained at 23±1 ºC from day 21 onwards or, (ii) conventional open-sided house (OH) with cyclic temperatures (minimum, 24 ºC; maximum, 34 ºC). Equal number of chicks of each housing system was subjected to either ad libitum feeding (AL) or 60% feed restriction on d 4, 5 and 6 (FR). On day 42, heterophil to lymphocyte ratios (HLR) were significantly lower in OH birds fed AL than those of CH. The CH birds had greater body weights, higher feed intake and better FCR than those of OH. Raising birds under OH, as measured by CORT, was more stressful than CH. The lower CORT in FR birds compared to their AL counterparts suggests improved heat tolerance in the former. Within the AL group, the OH chicks had lower HLR than CH and this could be associated with the more rapid growth rate in the latter. Raising birds in OH, where the birds were exposed to a wide variety of stimuli, shortened TI duration. The FR birds had shorter TI duration than their AL counterparts. In Experiment III, two trials were conducted to investigate the effects of housing system and early age feed restriction on CORT, HLR, heat shock protein (hsp) 70 expression and some blood parameters in response to either day (11:00 h) or night (20:00 h) transportation. Chicks were raised either in an (i) environmentally controlled chamber (CH) which was maintained at 23±1 ºC from day 21, or (ii) conventional open-sided house (OH) with cyclic temperatures (minimum, 24 ºC; maximum, 34 ºC). Equal number of chicks for each housing system was subjected to either ad libitum feeding (AL) or 60% feed restriction on d 4, 5 and 6(FR). On day 42, all the birds from each housing system-feeding regimen subgroup were subjected to road transport either at 11:00 h (Trial 1) or 20:00 h (Trial 2) for 6 hours (h) in open truck. Irrespective of time, transportation resulted in a marked elevation in HLR and CORT, The HLR and CORT data suggested that the magnitude of stress attributed to transportation increased with transit time. The chickens failed to habituate to stress following 6 h of transit. The OH chickens, as measured by HLR and CORT, were less distressed than their CH counterparts following crating and transportation. The improved ability of OH to cope with stress of transportation could be attributed to the greater hsp 70 response. Irrespective of time, FR dampened HLR reaction to transportation. For both day and night transportation, hsp 70 expression increased with transit time. Only day transportation had a consistent effect on serum levels of cholesterol, glucose and electrolytes. Chickens transported during the day had higher serum levels of sodium, chloride, glucose and cholesterol with transit time. In Experiment IV, two trials were conducted to investigate the effects of housing system and early age feed restriction on measurements of TI duration, meat quality and some blood parameters. Chicks raised either in an (i) environmentally controlled chamber (CH) which was maintained at 23±1 ºC from day 21 old, or (ii) conventional open-sided house (OH) with cyclic temperatures (minimum, 24 ºC; maximum, 34 ºC). Equal number of chicks from each housing system was subjected to either ad libitum feeding (AL) or 60% feed restriction on d 4, 5 and 6(FR). On day 42, all the birds from each housing system-feeding regimen were subgrouped to road transport either at 11:00 h (Trial 1) or 20:00 h (Trial 2) for 6 h in an open truck.For both day and night transportation, TI durations increased with transit time. The OH birds which were exposed to a wider variety of stimuli, as measured by TI duration, were less fearful than their CH counterparts. Birds subjected to FR and transported during day had shorter TI duration than those fed AL. Irrespective of transportation time, the muscle glycogen content of broilers reduced markedly following transportation. Higher muscle glycogen content was noticed in the OH birds compared to CH following both day and night transportation. Muscle pH declined with transit time in birds transported during the day. Similar response was not noticed among birds transported at night. Following 2 h of transportation, OH birds had lower muscle pH but the reverse was observed after 6 h of transit. Both day and night transportation reduced serum lactic acid levels. Among the AL birds, the day time transportation lowered serum levels of lactic acid but converse was noted following night transportation. While serum creatine kinase (CK) activity was not affected by duration of transportation, birds transported at night showed lower serum levels of CK with transit time. In Experiment V, the influence of pleasant and unpleasant experiences with human beings, and their combinations, on heat shock protein (hsp) 70 expression, and stress and fear responses in response to road transportation and disease resistance were studied in 750 day-old female broiler chicks. The pleasant treatment involved individual handling and gentle stroking for 30 sec daily from day 1 to 28 (PL). The unpleasant treatment involved individual handling, suspension by both legs, and exposure to noise (97 decibels) for 30 sec daily from day 1 to 28 (UNPL). The combination treatment involved exposure to either PL (day 1 to 14) and subsequently UNPL (day 15 to 28) or UNPL (day 1 to 14) and subsequently PL (day 15 to 28). On day 42, 60 birds per treatment were road transported for 3 h. Transportation resulted in higher HLR and CORT, and longer TI duration. The HLR of the PL birds was significantly lower than other groups. The CORT of PL and UNPL birds were not significantly different but lower than the other groups. Both PL-UNPL and UNPL-PL failed to attenuate HLR and CORT reactions following transportation. Although transportation had negligible effect on serum CK levels, the enzyme levels in PL birds were significantly lower than their control, PL-UNPL and UNPL counterparts. The PL and PL-UNPL birds were less fearful, as indicated by shorter TI duration. Irrespective of human treatment group, the amount of hsp 70 in the brain tissue was significantly higher following transportation. The hsp 70 reaction was significantly greater in the PL birds as compared to other groups. As measured by bursa to body weight ratio and bursal histological lesion score, human contact treatment had no consistent effect on resistance to infectious bursal disease. It can be concluded that subjecting birds to pre-slaughter processes which include handling by humans, crating and transportation elicited both stress and fear reactions, and changes in meat quality and hsp 70 expression. Subjecting birds to early age feed restriction, pleasant human contact and raising birds in conventional open-sided housing system can improve the ability of birds to cope with environmental insults.